Genomic landscape of adenoid cystic carcinoma of the breast. Issue 2 (14th July 2015) - Martelotto, Luciano G; De Filippo, Maria R; Ng, Charlotte KY; Natrajan, Rachael; Fuhrmann, Laetitia; Cyrta, Joanna; Piscuoglio, Salvatore; Wen, Huei‐Chi; Lim, Raymond S; Shen, Ronglai; Schultheis, Anne M; Wen, Y Hannah; et al.
Abstract Adenoid cystic carcinoma (AdCC) is a rare type of triple‐negative breast cancer (TNBC) characterized by the presence of the MYB–NFIB fusion gene. The molecular underpinning of breast AdCCs other than the MYB–NFIB fusion gene remains largely unexplored. Here we sought to define the repertoire of somatic genetic alterations of breast AdCCs. We performed whole‐exome sequencing, followed by orthogonal validation, of 12 breast AdCCs to determine the landscape of somatic mutations and gene copy number alterations. Fluorescence in situ hybridization and reverse‐transcription PCR were used to define the presence of MYB gene rearrangements and MYB–NFIB chimeric transcripts. Unlike common forms of TNBC, we found that AdCCs have a low mutation rate (0.27 non‐silent mutations/Mb), lack mutations in TP53 and PIK3CA and display a heterogeneous constellation of known cancer genes affected by somatic mutations, including MYB, BRAF, FBXW7, SMARCA5, SF3B1 and FGFR2. MYB and TLN2 were affected by somatic mutations in two cases each. Akin to salivary gland AdCCs, breast AdCCs were found to harbour mutations targeting chromatin remodelling, cell adhesion, RNA biology, ubiquitination and canonical signalling pathway genes. We observed that, although breast AdCCs had rather simple genomes, they likely display intra‐tumour genetic heterogeneity at diagnosis. Taken together, these findings demonstrate that the mutational burden and mutational repertoire of breast AdCCs are more similar to those of salivary gland AdCCs than to those of other types of TNBCs, emphasizing the importance of histological subtyping of TNBCs. Furthermore, our data provide direct evidence that AdCCs harbour a distinctive mutational landscape and genomic structure, irrespective of the disease site of origin. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.